Highly efficient yeast-based in vivo DNA cloning of multiple DNA fragments and the simultaneous construction of yeast/Escherichia coli shuttle vectors - Ei′ichi Iizasa; Yukio Nagano (BioTechniques)
In vivo recombinational cloning in yeast is a very efficient method. Until now, this method has been limited to experiments with yeast vectors because most animal, insect, and bacterial vectors lack yeast replication origins. We developed a new system to apply yeast-based in vivo cloning to vectors lacking yeast replication origins. Many cloning vectors are derived from the plasmid pBR322 and have a similar backbone that contains the ampicillin resistance gene and pBR322-derived replication origin for Escherichia coli. We constructed a helper plasmid pSU0 that allows the in vivo conversion of a pBR322-derived vector to a yeast/E. coli shuttle vector through the use of this backbone sequence. The DNA fragment to be cloned is PCR-amplified with the addition of 40 bp of homology to a pBR322-derived vector. Cotransformation of linearized pSU0, the pBR322-derived vector, and a PCR-amplified DNA fragment, results in the conversion of the pBR322-derived vector into a yeast/E. coli shuttle vector carrying the DNA fragment of interest. Furthermore, this method is applicable to multifragment cloning, which is useful for the creation of fusion genes. Our method provides an alternative to traditional cloning methods.